Feasibility Study Diploma In Health Department Analyst III Nutrition Semarang Health Polytechnic - Surati Surati; Soesanto Soesanto; Sri Hetty Susetyorini (UPPM Poltekkes Kemenkes Semarang, 2015)
In order to develop MOH Polytechnic upanya Semarang and participate in development, especially in the field of health care and to maximize the potential that exists in the Polytechnic it is necessary to add a new department at the Polytechnic, which is preceded by a feasibility study of the implementation of the Diploma Health Analyst.  Feasibility study done on the campus III by analyzing the needs of the Department of Nutrition Programs Analyst dididang availability of infrastructure and human resources in the department of Nutrition and conduct a comparative study to the Department of Health in Central Java Analyst.  Analyst III feasibility study Diploma in Health Nutrition Department of Health Polytechnic Semarang have common goals Developing Health Programs Analyst at Ministry of Health Polytechnic Semarang as well as participate in the development efforts in the field of Health Care. Develop specific goals and polytechnic MOH Semarang by adding Analyst Department of Health and Maximizing the potential of the polytechnic MOH Semrang.  Human Resources (Lecturer) in the Department of Nutrition of the first semester to the second semester 66% as taught in the Department of Health Analyst and only 34% of faculty from other institutions. Lecturer / Lecturer consists of: 23 permanent lecturers, lecturers are not fixed 6, 6 Administration, 11 contract staff, 4 guards (2 PNS and 2 contracts) and educational facilities at the Department of Health Polytechnic Semarang Analyst covering : Area of land and Status: 24 629 m2 owned by the Department of Health.  Classroom use of the Department of Nutrition at a maximum of 6 hours each day so that they can be used for classroom Analyst Department of Health. The use of laboratory space Nutrition Department every day up to 4 hours so that they can be used for laboratory practice Analais Department of Health. Need for additional clinical and laboratory hematology and tools and additional classrooms, administrative and secretarial personnel manager for Health Analysis. Diploma Analyst III Department of Health was established in the Department of Nutrition feasible.